RELATIONSHIP OF THERAPEUTIC COMMUNICATION OF NURSES TO PATIENT SATISFACTION - Tumiwa, Angelia Sendi; Warouw, Herman; Memah, Herlina (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: Nurse interactions using therapeutic communication are generally more than half as good but patient satisfaction is still lacking. Communication applied by nurses greatly influences patient satisfaction, if nurses cannot communicate properly it will have an impact on patient dissatisfaction. Objective: literature review to determine nurse communication on patient satisfaction. Method: This research uses a literature review type. Search for articles published in national journals using the Google Scholar database using the keywords nurse communication, patient satisfaction. With journal provisions, namely from 2016-2020 and determining 6 journals that are in accordance with the topic of discussion of the literature review. Results: based on six literature reviews, the research results showed that most nurses had good communication with patients so that on average, patients were satisfied with nursecommunication. Based on the results of the research and discussion that was carried out, it was concluded that the communication carried out by the nurse was good enough so that the average patient was satisfied with the communication provided by the nurse. Suggestion: Nurses need to realize that communication is very important in improving the quality of nursing services, therefore nurses must further improve good communication with patients.